Seroprevalence of the novel swine acute diarrhea syndrome coronavirus in China assessed by enzyme-linked immunosorbent assay - Liu, Zuqing; Zhao, Ya; Yang, Jingyu; Liu, Xi; Luo, Yun; Zhu, Lili; Huang, Kun; Sheng, Feng; Du, Xuezhu; Jin, Meilin (Frontiers in Cellular and Infection Microbiology, 2024)
The endemic outbreak of SADS-CoV has resulted in economic losses and potentially threatened the safety of China's pig industry. The molecular epidemiology of SADS-CoV in pig herds has been investigated in many provinces in China. However, there are no data over a long-time span, and there is a lack of extensive serological surveys to assess the prevalence of SADS-CoV in Chinese swine herds since the discovery of SADS-CoV. In this study, an indirect anti-SADS-CoV IgG enzyme-linked immunosorbent assay (ELISA) based on the SADS-CoV S1 protein was established to investigate the seroprevalence of SADS-CoV in Chinese swine herds. Cross-reactivity assays, indirect immunofluorescence, and western blotting assays showed that the developed ELISA had excellent SADS-CoV specificity. In total, 12,978 pig serum samples from 29 provinces/municipalities/autonomous regions in China were tested from 2022 to 2023. The results showed that the general seroprevalence of SADS-CoV in China was 59.97%, with seroprevalence ranging from 16.7% to 77.12% in different provinces and from 42.61% to 68.45% in different months. SADS-CoV is widely prevalent in China, and its seroprevalence was higher in Northeast China, North China, and Central China than in other regions. Among the four seasons, the prevalence of SADS-CoV was the highest in spring and the lowest in autumn. The results of this study provide the general seroprevalence profile of SADS-CoV in China, facilitating the understanding of the prevalence of SADS-CoV in pigs.More importantly, this study is beneficial in formulating preventive and control measures for SADS-CoV and may provide directions for vaccine development.